Grammatical Errors in Intisari Pelajaran Bahasa Inggris 2013 from Buku Jagoan: Langsung Lulus UASBN SD /MI 2013 - Murniati Murniati (Journal of English Language and Culture, 2017)
There a lot of prediction test books sold in the bookstores in Indonesia. Before doing the national final test, the students may study first from the summary provided in those prediction test books. If the lessons are incorrect, such as containing grammatical errors, most probably, the results of the test are not good. Unfortunately, this happens not because the students’ ability but because of the lessons provided themselves. This research aims to find the grammatical errors found in the summary of English lessons in Buku Jagoan: Langsung Lulus UASBN SD /MI 2013. There are four kinds of errors which are going to be observed, namely the omission, additions, misformation, and misordering. In this research, all sentences provided in the summary are going to be analyzed. The errors will be identified and classified; then, the correction is made. The result of the research  has shown that the four kinds of errors have been found in the summary of English lessons in Buku Jagoan: Langsung Lulus UASBN SD /MI 2013. Keywords: grammatical errors, omission, additions, misformation, misordering